Industrial Perspective on Deep Brain Stimulation: History, Current State, and Future Developments - Sarem-Aslani, Ali; Mullett, Keith (Frontiers in Integrative Neuroscience, 2011)
Deep Brain Stimulation (DBS) emerged in the late 1960’s as a possible therapeutic alternative to lesioning in patients with severe, chronic, intractable pain. DBS devices in the era were based on cardiac pacing technology but were greatly modified in implementation due to the unique needs of DBS. Clinical studies in the 1970’s and early 1980’s revealed a technique with modest results which did not lead to regulatory approval for the treatment of pain. In the 1980’s a new application for DBS emerged in the treatment of movement disorders. Clinical trials confirmed the robustness of the therapy leading to approvals by regulatory authorities in the US and Europe for the treatment of tremor and the symptoms of Parkinson’s disease. Technology based on that used for earlier clinical research in pain was improved by leveraging advances in cardiac pacing technology resulting in the sophisticated and reliable systems available today. In the 1990’s scientific exploration began in the treatment of psychiatric disorders which is ongoing today. Simultaneously, studies into the treatment of epilepsy were begun which resulted in regulatory approval in Europe. Suggestions have been made to expand these scientific explorations to other central nervous system dysfunctions. Opportunity remains to improve the technology including individualized and symptom specific stimulation patterns, more physician and patient friendly programming and possibly closed loop systems for more situation dependent and effective therapy.